Make A Match Learning Model on Learning Outcomes in Elementary Schools: A Bibliometric Analysis - Muslikah, Aliyah; Amriyah, Chairul; Ningrum, Ayu Reza (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This article will map the architecture and detect trends in scholarly papers on the Make a Match (MaM) Learning Model in Elementary Schools from 2020 to 2025. The goals of this study are to examine annual publication growth, identify the most prolific journals, map significant keyword networks, and detect new topic trends in this literature. The study employed bibliometrics. Data were obtained using Publish or Perish software from Google Scholar, Crossref, and OpenAlex by searching the keywords "make a match," ("hasil belajar" or "learning outcome"), and ("sd" or "elementary school"). We reviewed and examined 130 items from 582 documents. VOSviewer created network, overlay, and density visualizations. The results showed that: (1) Publication Growth: There was a significant and accelerating increase in publications, reaching a peak in 2024 (36 documents, or 28%). (2) Central Focus: The main keywords are “Learning Outcomes” (56 occurrences, TLS 77) and “Make a Match” (52 occurrences, TLS 65), confirming a strong relationship between the two variables. (3) Topic Concentration: The density visualization highlights the two highest concentration areas: “learning outcomes” with “mathematics” and “make a match” with “make a match learning model.” (4) Development Trend: The overlay visualization shows a shift from basic studies (blue/green, 2022–2023) to topic specialization, which is shown by the rise of terms like "Islamic education" (yellow, 2023–2024). This study empirically supports the Make a Match Learning Model as the best pedagogical intervention to improve primary school learning outcomes in 2020–2025. These findings outline the mathematics focus and provide new topic development opportunities for future academics and practitioners.